2017
DOI: 10.3389/fpsyg.2017.01494
|View full text |Cite
|
Sign up to set email alerts
|

Position Affects Performance in Multiple-Object Tracking in Rugby Union Players

Abstract: We report an experiment that examines the performance of rugby union players and a control group composed of graduate student with no sport experience, in a multiple-object tracking task. It compares the ability of 86 high level rugby union players grouped as Backs and Forwards and the control group, to track a subset of randomly moving targets amongst the same number of distractors. Several difficulties were included in the experimental design in order to evaluate possible interactions between the relevant va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…In accordance with the literature ( Faubert, 2013 ; Martín et al, 2017 ; Qiu et al, 2018 ; Harris et al, 2020a ; Jin et al, 2020 ), visual tracking performance was higher in soccer players than in non-soccer players regardless of movement type. These findings supported the idea that soccer players have higher core perceptual-cognitive abilities like visual attention ( Voss et al, 2010 ; Qiu et al, 2018 ; Jin et al, 2020 ) or working memory ( Green and Bavelier, 2006 ; Harris et al, 2020a ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with the literature ( Faubert, 2013 ; Martín et al, 2017 ; Qiu et al, 2018 ; Harris et al, 2020a ; Jin et al, 2020 ), visual tracking performance was higher in soccer players than in non-soccer players regardless of movement type. These findings supported the idea that soccer players have higher core perceptual-cognitive abilities like visual attention ( Voss et al, 2010 ; Qiu et al, 2018 ; Jin et al, 2020 ) or working memory ( Green and Bavelier, 2006 ; Harris et al, 2020a ).…”
Section: Discussionsupporting
confidence: 91%
“…In relation to the sports domain, inter-individual differences were also found between practitioners and non-practitioners of team sports ( Qiu et al, 2018 ; Harris et al, 2020a ; Jin et al, 2020 ). However, this effect seemed to be moderated by the level of practice ( Faubert, 2013 ; Qiu et al, 2018 ) and the players position on the field ( Mangine et al, 2014 ; Martín et al, 2017 ). The study by Memmert et al (2009) was the only one to not find any differences between groups on an MOT task.…”
Section: Introductionmentioning
confidence: 95%
“…NeuroTracker has since been developed as a training tool to improve cognitive functions including attention, working memory, and visual processing speed (Parsons et al, 2016 ). This technology has potential application for testing and training cognitive function in athletes (Martin et al, 2017 ) and individuals with concussion (Corbin-Berrigan et al, 2018 ), and improving biological perception of motion in the elderly (Legault and Faubert, 2012 ). The NeuroTracker application has not been validated.…”
Section: Technologies For Monitoring Psychological Stress and Evaluatmentioning
confidence: 99%
“…This finding indicates that basketball players have a marked advantage over nonathletic college students in attention to processing speed in multitarget tracking tasks. Martín et al (2017) investigated attention between rugby players who played different positions in the game and non-athletes by adjusting the target speed in the MOT task. Their results showed that the visual tracking performance of rugby players in defender positions is significantly better than that of both players in forward positions and in non-athletes.…”
Section: Visual Tracking Performance Associated With Target Speedmentioning
confidence: 99%
“…Faubert (2013) showed that professional athletes are much better than sub-elites and novices to process complex dynamic visual scenes. Martín et al (2017) used the MOT task and found that the tracking performance of rugby players in the back positions is better than that of those in the forward positions and better than that of undergraduate students. All of the aforementioned studies have used the MOT task to show that expertise in visual attention provides certain advantages.…”
Section: Introductionmentioning
confidence: 99%